An Analysis on Different Techniques Highly Secure Biometrics Voting System: Enhancing Security and Authentication in Electronic Voting Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A voting system in which election figures is documented, kept and managed as digital facts is called an electronic voting system. An e-voting system has two categories on-line e-voting and offline e-voting. On-line e-voting done using internet and offline e-voting done using by a voting machine or ballet papers. The main challenge of e-voting is authentication of voters, safety of voting method, locking voted figures. It is the major reason why a protected e-voting method is very essential. In this paper i have discussed the validating voters and polling data safety characteristics for e-voting. For make sure that vote casting cannot be changed by unofficial person. The voter verification in online e-voting procedure can be through by prescribed registration through officers and by entering otp. In offline e-voting procedure verification can be done using iris reorganization, finger vein sensing which permits the electronic ballot reorganize for permitting voters to cast their votes. The voted data and voter’s details with cryptography technique received at database administration unit (dau) using timely manner using gsm system.I have proposed an online e-voting system with protected verification which is provided by biometric as well as password safety to voter accounts. On the basis of core image the secret key merge with the cover image is basic idea. Outcome of this process produces a stego image which looks quite similar to the cover image. The core image is a biometric measure and stego image is take out at the server side to accomplish the voter verification purpose. This system decreases the threats as the hackers have to find both secret key and template that sorts the election process to be safe and healthy.